2008
DOI: 10.1074/jbc.m803525200
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and in Vitro Examination of Stability of Primary Hyperoxaluria-associated Human Alanine:Glyoxylate Aminotransferase

Abstract: Primary hyperoxaluria type I is a severe kidney stone disease caused by mutations in the protein alanine:glyoxylate aminotransferase (AGT). Many patients have mutations in AGT that are not deleterious alone but act synergistically with a common minor allele polymorphic variant to impair protein folding, dimerization, or localization. Although studies suggest that the minor allele variant itself is destabilized, no direct stability studies have been carried out. In this report, we analyze AGT function and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 54 publications
5
45
2
Order By: Relevance
“…Second, the difference in stability between holo and apo is similar for AGT-Ma and AGT-Mi. This is in apparent contrast with what is recently claimed by Hopper et al (5). These authors state that AGT-Ma is stabilized by PLP to a greater extent than AGT-Mi.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Second, the difference in stability between holo and apo is similar for AGT-Ma and AGT-Mi. This is in apparent contrast with what is recently claimed by Hopper et al (5). These authors state that AGT-Ma is stabilized by PLP to a greater extent than AGT-Mi.…”
Section: Resultscontrasting
confidence: 56%
“…Recent "in vitro" and "in vivo" studies have established that AGT-Mi is less stable and active than AGT-Ma (5). It has also been reported that some variants (G170R, I244T, F152I) encoded on the background of the minor allele have reduced steady-state protein levels, and it has been hypothesized that this reduction could be largely due to protein destabilization (5). However, although PLP seems to stabilize, even to a different extent, both AGT-Ma and AGT-Mi, it does not appear to have any stabilizing effect on the PH1-causing variants (5).…”
mentioning
confidence: 99%
“…We next analyzed alleles of AGT associated with PH1, including a minor allele polymorphic variant (AGTmi, with amino acid substitutions P11L and I340M), and a disease variant associated with the minor allele, I244T (AGTmi I244T ). AGTmi has a mild destabilizing effect, while the AGTmi I244T disease variant has greatly reduced stability (Lumb and Danpure 2000;Hopper et al 2008;Cellini et al 2010a). Using IDESA, we observed robust differences in growth of yeast expressing these variants, with yeast expressing AGTmi and AGTmi I244T showing poorer growth than yeast expressing wild-type AGT and yeast expressing AGTmi I244T showing a temperature-sensitive phenotype at 37° (Figure 1, B and C).…”
Section: Analysis Of Disease Variants Using Idesamentioning
confidence: 87%
“…For proteins with unknown or undefined functions, identification of disease variants that affect activity but not stability can provide clues to their mechanisms of action. We chose 35 disease variants of AGT from PH1 patients (Williams et al 2009) that showed loss of function (,10% of wild-type AGT activity) in a yeast activity assay based on complementation (Hopper et al 2008). Within this set, we identified 12 mutants that showed good stability in IDESA ( Figure 4B, top), but poor activity in the complementation assay ( Figure 4B, bottom).…”
Section: Characterization Of Uncharacterized Disease Alleles Of Agtmentioning
confidence: 99%
See 1 more Smart Citation